Dilemas da escola inclusiva - Souza, Célia Magalhães de (2006)
This research, focusing on the inclusion questions, aims to analyze whether, in the teach-learning process, the pedagogical actions developed by the teacher, mediated by languages and other cultural tools socially built in the school environment, are able to promote: (1) the social constitutions of pupils that features NEE, as well as, (2) the perception of themselves and the other pupils. Furthermore, it discusses the existing dilemmas in the inclusive school, represented in the terminology used in legislation as well as in pedagogical actions developed by the teacher. During the teaching process, when stipulating the rules and the division of work, the teacher creates such a conflict that may lead to a transformation in the activity and in the social practices developed in the school environment. In a broader view, this thesis intends to contribute to the formation area of the teacher that seeks to dissipate such dilemmas, allowing, in this way, the inclusion of the pupils with special educational needs. This work is supported by theories which include the studies on both verbal and writing speeches developed by Bakhtin (1979), teach-learning and defectology developed by Vygotsky (1920-1930) and Theory of the Activity developed by Engeström (1999). The research methodology used is the participatory one (Rizzini, et al. 1999). This research is carried out in a public school of the capital of São Paulo and it has, as a participant of the process, a pupil with special educational needs and a diagnosis of cerebral paralysis. Besides the coordination problems and speaking difficulties, such pupil presents a slight mental deficiency. The data were collected in 2004 through a) observation; b) recording of the classes in audio and video; c) interviews. The results demonstrate that in order to propitiate a real inclusion, the so-called inclusive school has to face the challenge of rethinking its pedagogical practice. This rethinking has to be oriented in the forms of collaborative action and, gradually, determine the level of the child development allowing a movement of building and rebuilding the pedagogical actions in which teachers and pupils may plan together the tasks to be performed